Administrative Personnel Strategies in Improving the Quality of Education Services - Maulidia, Dinda Nur; Walid, Muhammad; Triwiyanto, Teguh (Proceedings Series of Educational Studies, 2024)
Educational services in educational institutions often face challenges related to the performance of administrative personnel, which has an impact on the quality of educational services. This study aims to analyze the strategies applied by administrative staff in improving the quality of education services. Using a qualitative research method with a literature study approach, this study reviewed several journals and reports related to education management. The results show that an effective strategy involves three main stages, namely strategy formulation, implementation and evaluation. Supporting factors for administrative staff performance include government policy support, adequate technology and continuous training, while inhibiting factors include lack of training, resistance to new technology and limited infrastructure in remote areas. This research confirms the importance of implementing comprehensive strategies to improve the quality of administrative services, which has a positive impact on student achievement and the overall effectiveness of the education process.